Salt-Sensitive Signaling Networks in the Mediation of K+/Na+ Homeostasis Gene Expression in Glycyrrhiza uralensis Roots - Lang, Tao; Deng, Shurong; Zhao, Nan; Deng, Chen; Zhang, Yinan; Zhang, Yanli; Zhang, Huilong; Sa, Gang; Yao, Jun; Wu, Caiwu; Wu, Yanhong; Deng, Qun; et al. (Frontiers in Plant Science, 2017)
We investigated the effects of salt-sensitive signaling molecules on ionic fluxes and gene expression related to K+/Na+ homeostasis in a perennial herb, Glycyrrhiza uralensis, during short-term NaCl stress (100 mM, 24 h). Salt treatment caused more pronounced Na+ accumulation in root cells than in leaf cells. Na+ ions were mostly compartmentalized in vacuoles. Roots exposed to NaCl showed increased levels of extracellular ATP (eATP), cytosolic Ca2+, H2O2, and NO. Steady-state flux recordings revealed that these salt-sensitive signaling molecules enhanced NaCl-responsive Na+ efflux, due to the activated Na+/H+ antiport system in the plasma membrane (PM). Moreover, salt-elicited K+ efflux, which was mediated by depolarization-activated cation channels, was reduced with the addition of Ca2+, H2O2, NO, and eATP. The salt-adaptive effects of these molecules (Na+ extrusion and K+ maintenance) were reduced by pharmacological agents, including LaCl3 (a PM Ca2+ channel inhibitor), DMTU (a reactive oxygen species scavenger), cPTIO (an NO scavenger), or PPADS (an antagonist of animal PM purine P2 receptors). RT-qPCR data showed that the activation of the PM Na+/H+ antiport system in salinized roots most likely resulted from the upregulation of two genes, GuSOS1 and GuAHA, which encoded the PM Na+/H+ antiporter, salt overly sensitive 1 (SOS1), and H+-ATPase, respectively. Clear interactions occurred between these salt-sensitive agonists to accelerate transcription of salt-responsive signaling pathway genes in G. uralensis roots. For example, Ca2+, H2O2, NO, and eATP promoted transcription of GuSOS3 (salt overly sensitive 3) and/or GuCIPK (CBL-interacting protein kinase) to activate the predominant Ca2+-SOS signaling pathway in salinized liquorice roots. eATP, a novel player in the salt response of G. uralensis, increased the transcription of GuSOS3, GuCIPK, GuRbohD (respiratory burst oxidase homolog protein D), GuNIR (nitrate reductase), GuMAPK3, and GuMAPK6 (the mitogen-activated protein kinases 3 and 6). Moreover, GuMAPK3 and GuMAPK6 expression levels were enhanced by H2O2 in NaCl-stressed G. uralensis roots. Our results indicated that eATP triggered downstream components and interacted with Ca2+, H2O2, and NO signaling to maintain K+/Na+ homeostasis. We propose that a multiple signaling network regulated K+/Na+ homeostasis in NaCl-stressed G. uralensis roots.